2008
DOI: 10.1002/pssb.200743111
|View full text |Cite
|
Sign up to set email alerts
|

Low‐temperature electrical resistivity of cupric telluride (CuTe) thin films

Abstract: Thin films of cupric telluride (CuTe) of thickness from 50 to 200 nm have been prepared using a thermal evaporation technique onto well‐cleaned glass substrates kept at 300 K under a vacuum better than 2 × 10–5 mbar. After annealing the deposited films at 375 K for an hour, the resistivity of these films and that of bulk CuTe were measured using the four‐probe technique as a function of temperature from 80 to 310 K. It is found that the bulk sample of CuTe exhibits metallic behaviour and the thin films show se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
2
9
0
1
Order By: Relevance
“…Figure 7 shows the variation of ( ℎ]) 2 with ℎ] for deposited CuTe and Cu 2 Te. By extrapolating straight line portion of ( ℎ]) 2 against ℎ] plot to = 0, the optical band gap energy was found to be 1.51 eV for CuTe and 1.12 eV for Cu 2 Te films, comparable with the value reported earlier for CuTe and Cu 2 Te thin film [1,15].…”
Section: Sem Observationssupporting
confidence: 86%
See 2 more Smart Citations
“…Figure 7 shows the variation of ( ℎ]) 2 with ℎ] for deposited CuTe and Cu 2 Te. By extrapolating straight line portion of ( ℎ]) 2 against ℎ] plot to = 0, the optical band gap energy was found to be 1.51 eV for CuTe and 1.12 eV for Cu 2 Te films, comparable with the value reported earlier for CuTe and Cu 2 Te thin film [1,15].…”
Section: Sem Observationssupporting
confidence: 86%
“…In these experiments, the potential scanning was started at 0 V to avoid the oxidative stripping of Cu. Similar to most literatures, two reduction peaks are seen: peak C2 at about −0.21 V based upon the four-electron process for Te reduction shown in reaction (1) and peak C3 at about −0.46 V, which should be corresponded to bulk Te (0) reduction to Te 2− , as reaction (2) shows…”
Section: Cute Thin Film Depositionsupporting
confidence: 86%
See 1 more Smart Citation
“…No manifestation of a Peierls-like distortion of the Te chains has previously been found for this compound, and metallic conductivity was determined experimentally. [4,5] In recent X-ray diffraction experiments on single crystals, however, we discovered that the structure of CuTe indeed exhibits a charge density wave (CDW)-type modulation. The modulation leads to a significantly different bonding situation as compared to the average or non-modulated structure.…”
mentioning
confidence: 99%
“…In the present work the film deposited at 500 C shows relatively low resistivity of 1.36 10 -3  cm. Neyvasagam et al [23] reported electrical resistivity of CuTe thin film is in the range of 3.45  10 -1  cm -4.693  10 -1  cm. Pathan et al [5] reported dark electrical resistivity for the mixed phase film (CuTe, Cu 2 Te and Cu 2-x Te) measured at RT is of the order of 10  cm.…”
Section: Electrical Propertiesmentioning
confidence: 97%